Conservation Treatment and the Custodian/Conservator Relationship - Barbara Appelbaum (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Collaboration between conservators and custodians is an important part of conservation treatment planning, particularly while deciding on the treatment goal. Custodians need to understand more about the treatment decision-making process in order to participate in a meaningful way and to assure that treatment decisions are consistent with the current use, meaning, and values of a work of art.  Meaningful collaboration is, however, rare, made difficult by a lack of understanding among the parties, and exacerbated by conservators’ habitual use of technical language.  It is possible – and desirable - for conservators to discuss the treatment decision-making process using non-technical terminology so that real collaboration can take place.